2012
DOI: 10.1111/and.12025
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of date palm (Phoenix dactyliferaL.) pollen extract on cadmium-induced testicular toxicity

Abstract: Cadmium (Cd) is a well-known testicular toxicant. This study was designed to explore the long-term effects of a single low dose of Cd on spermatogenesis, and testicular dysfunction and oxidative stress, and the therapeutic potential of date palm pollen extract (DPP) in averting such reproductive damage. Adult male Wistar rats received a single intraperitoneal injection of CdCl2 (0 or 1 mg kg(-1) ). Twenty-four hours later, they started receiving DPP (0 or 40 mg kg(-1) ) orally, once daily for 56 consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
47
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 43 publications
9
47
0
1
Order By: Relevance
“…The results indicated that Cd significantly (p < 0.05) reduced the volume of testis, carrying capacity and the epididymal length. These effects may be associated with a reduction in serum testosterone levels as earlier postulated by El-Neweshy, El-Maddawy, and El-Sayed (2013). This findings which are consistent with previous reports (Qadori & Al-Shaikh, 2011;El-Neweshy et al, 2013;Saeed, 2013;Zakaria & AlBusadah, 2015) confirm the toxic effect of Cd on the testis.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The results indicated that Cd significantly (p < 0.05) reduced the volume of testis, carrying capacity and the epididymal length. These effects may be associated with a reduction in serum testosterone levels as earlier postulated by El-Neweshy, El-Maddawy, and El-Sayed (2013). This findings which are consistent with previous reports (Qadori & Al-Shaikh, 2011;El-Neweshy et al, 2013;Saeed, 2013;Zakaria & AlBusadah, 2015) confirm the toxic effect of Cd on the testis.…”
Section: Resultssupporting
confidence: 91%
“…These effects may be associated with a reduction in serum testosterone levels as earlier postulated by El-Neweshy, El-Maddawy, and El-Sayed (2013). This findings which are consistent with previous reports (Qadori & Al-Shaikh, 2011;El-Neweshy et al, 2013;Saeed, 2013;Zakaria & AlBusadah, 2015) confirm the toxic effect of Cd on the testis. Cd has been reported to induce necrotic degenerative changes in the testis (Predes et al, 2010) and destruction of testicular germ cells due to membrane damage or macromolecular degeneration (Qadori & Al-Shaikh, 2011).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations